INFORMATION TECHNOLOGIES OF MEASURING OF GEOMETRICAL SIZES OF AVIATION DETAILS - Babak, Vitaliy; Kvasnikov, Volodymyr; Borkovskaya, Lyubov (Proceedings of National Aviation University (archive), 2006)
The method of the high-fidelity automatic measuring of rotation surfaces on a co-ordinate-measuring machine is developed in this article. The mathematical model of error of measuring of high-precision details is developed and treatment of real interferogram is conducted.